PERAN PEMODERASI KEPEMILIKAN INSTITUSIONAL ATAS PENGARUH PERENCANAAN PAJAK, UKURAN PERUSAHAAN DAN ARUS KAS OPERASI TERHADAP BIAYA HUTANG - Renato Sitompul Sitompul (Universitas Pelita Harapan, 2023)
The purpose of this study is to analyze the effect of the tax planning, firm size and cash flow operation on company’s cost of debt with institutional ownership as the moderation. This study design is using an explanatory method with quantitative approach. This study uses secondary data sources, such as data of the company's financial statements in the form of balance sheet, profit and loss, cash flow. The sample in this study is the companies in index LQ45 listed in Indonesia Stock Exchange 2014-2018. Data that obtained analyzed by multiple linear regression analysis. The Result of this study states that, there is the negative impact and significant of tax planning, firm size and cash flow operation to cost of debt. The result also to showed that institutional ownership have strenghtening by firm tax planning dan cash flow operation on cost of debt, while institutional ownership can not strengthen the negative impact the relationship between firm size with the cost of debt.